Islamic Ethics: an outline of its principles and scope - Hashi, Abdurezak Abdulahi (Kulliyyah of Science, IIUM, 2011)
Islamic ethics is the ethical system formed by the teachings of the Qur’an and explained by the Prophet (s.a.w) through action and words. This paper aims to offer analytical study of Islamic ethics based on the Qur’an and Sunnnah. The paper also attempts to offer an introductory exposition on the conceptual framework and scope of Islamic ethics. To present the conceptual framework and scope of Islamic ethics, the Qur’anic terms and the Prophetic pronouncements related to the subject are exposed, and the opinions of the Muslim exegetes of the Qur’an as well as the opinions of Muslim jurists related to the subject are unveiled. Keywords: Islamic ethics, principles, scope, analysis